How did West Bengal bell the proverbial cat of agricultural metering?: the economics and politics of groundwater. - Mukherji, Aditi; Das, A. (International Water Management Institute, 2012)
West Bengal had started a program of metering of agricultural tube wells in 2007. Since then, the state has successfully metered almost 90 percent of its electric tube wells. This comes at a time when most other states in India have steered clear of metering even though universal metering is mandatory according to the Electricity Act of 2003. Why is it then that the government of West Bengal succeeded when others floundered? This paper offers answers in terms of economics of metering and agrarian politics and discourses surrounding groundwater in the state. It also suggests a few generic steps that other states may adopt in their quest for universal metering. West Bengal had started a program of metering of agricultural tube wells in 2007. Since then, the state has successfully metered almost 90 percent of its electric tube wells. This comes at a time when most other states in India have steered clear of metering even though universal metering is mandatory according to the Electricity Act of 2003. Why is it then that the government of West Bengal succeeded when others floundered? This paper offers answers in terms of economics of metering and agrarian politics and discourses surrounding groundwater in the state. It also suggests a few generic steps that other states may adopt in their quest for universal metering. West Bengal had started a program of metering of agricultural tube wells in 2007. Since then, the state has successfully metered almost 90 percent of its electric tube wells. This comes at a time when most other states in India have steered clear of metering even though universal metering is mandatory according to the Electricity Act of 2003. Why is it then that the government of West Bengal succeeded when others floundered? This paper offers answers in terms of economics of metering and agrarian politics and discourses surrounding groundwater in the state. It also suggests a few generic steps that other states may adopt in their quest for universal metering.